1994
DOI: 10.1002/j.1460-2075.1994.tb06365.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the CD3 eta locus causes high lethality in mice: modulation of Oct-1 transcription on the opposite strand.

Abstract: CD3 zeta and eta chains are components of the T cell antigen receptor (TCR) complex and are transcribed from a common gene by alternative splicing. TCR complexes containing the zeta eta dimer have been thought to mediate different functions than complexes containing the zeta 2 dimer. To analyze the role of eta in the development and function of T cells, we generated eta‐deficient mice without affecting zeta by gene targeting in embryonic stem cells. Homozygous mutant embryos developed normally. Unexpectedly, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Concerning differences between the phenotype of the KO mice in this paper and those of the preceding papers, we consider it may be due to a difference in the structure of the targeting vectors because similar discrepancies were reported several times in the past (Ohno et al, 1994;Olson et al, 1996). In these cases, a difference in the position or direction of the promoter and drug resistance gene was reported to affect the expression or splicing of neighboring genes.…”
Section: Discussionmentioning
confidence: 57%
“…Concerning differences between the phenotype of the KO mice in this paper and those of the preceding papers, we consider it may be due to a difference in the structure of the targeting vectors because similar discrepancies were reported several times in the past (Ohno et al, 1994;Olson et al, 1996). In these cases, a difference in the position or direction of the promoter and drug resistance gene was reported to affect the expression or splicing of neighboring genes.…”
Section: Discussionmentioning
confidence: 57%
“…Because it is difficult to reconcile the function of a nuclear DNA polymerase with a defect in axonemal structure (missing IDA), we examined the deletion construct in more detail and determined that another gene was also likely disrupted in the mouse model. Other reports have also documented the disruption of more than one gene in mouse models (22,23). Therefore, the results from any genetically modified animal should be interpreted with caution, especially if the phenotype observed does not agree with the known function of the targeted gene.…”
Section: Discussionmentioning
confidence: 91%
“…Sequencing the exon-intron boundaries of mouse exons 3 to 7 and comparison to known human sequences (59) showed that the genomic organization was conserved. Previous studies have shown that targeted disruption of exon 9 in the CD3 locus also affected Oct-1 transcription due to overlap of the 3Ј regions of the two genes (28,31,41). To avoid disrupting the CD3 locus, a strategy was designed to inactivate Oct-1 by targeting the 5Ј end.…”
Section: Resultsmentioning
confidence: 99%